Screening for severe anaemia in pregnancy in Kenya, using pallor examination and self-reported morbidity. - Shulman, C; Levene, M; Morison, L; Dorman, E; Peshu, N; Marsh, K (2001)
Severe anaemia in pregnancy is an important preventable cause of maternal and perinatal morbidity and mortality. Different methods of screening for severe anaemia in pregnancy were evaluated in a 2-phased study conducted in Kilifi, Kenya. In phase 1 (in 1994/95), pallor testing was evaluated alone and in addition to raised respiratory/pulse rates: 1787 pregnant women were examined by one of 2 midwives. Sensitivities for detecting severe anaemia (haemoglobin < 7 g/dL) were 62% and 69% and specificities 87% and 77%, respectively for each of the midwives. Addition of high pulse rate increased sensitivity to 77% and 81%, but specificity reduced to 60% and 51%, respectively. In phase 2, following qualitative in-depth work, a screening questionnaire was developed. An algorithm based on screening questions had 80% sensitivity and 40% specificity. Midwife pallor-assessment was conducted following the screening questionnaire. In this phase (conducted in 1997), the midwife performed very highly in detecting severe anaemia, achieving sensitivity of 84% and specificity of 92%. Spending a few minutes asking women questions may have improved the ability to interpret pallor findings. This study demonstrates the value of pallor testing and raises alternative approaches to improving it.